An Accelerated Test Method of Simultaneous Carbonation and Chloride Ion Ingress: Durability of Silica Fume Concrete in Severe Environments - S. A. Ghahari; A. M. Ramezanianpour; A. A. Ramezanianpour; M. Esmaeili (Advances in Materials Science and Engineering)
The effects of simultaneous carbonation and chloride ion attack on mechanical characteristics and durability of concrete containing silica fume have been investigated through an accelerated test method. Specimens containing different amounts of silica fume were maintained in an apparatus in which carbon dioxide pressure and concentration and relative humidity were kept constant, and wetting and drying cycles in saline water were applied. Surface resistivity, sorptivity, CO2 consumption, and carbonation and chloride ion ingress depths measurements were taken. Phase change due to carbonation and chloride ion attack was monitored by XRD analysis, and microstructures and interfacial transition zones were studied by implementing SEM as well as mercury intrusion porosimetry. It was expected to have a synergistic effect in the tidal zone where simultaneous carbonation and chloride ion attack happen. However, the observed reduced surface resistivity, compared to specimens maintained in CO2 gas, could be due to the moisture that is available near the surface, hindering CO2 from penetrating into the pores of the specimens. Moreover, the porosity analysis of the specimens showed that the sample containing silica fume cured in the tidal zone had 50.1% less total porosity than the plain cement paste cured in the same condition.